Non-Clinical Pharmacokinetic/Pharmacodynamic and Early Clinical Studies Supporting Development of a Novel Subcutaneous Formulation for the Monoclonal Antibody Rituximab - Bittner, B.; Richter, W. F.; Hourcade-Potelleret, F.; Herting, F.; Schmidt, J. (Drug Research, 2014)
This overview article describes the non-clinical pharmacology, pharmacokinetic and clinical dose-finding programs supporting the development of a novel subcutaneous formulation for rituximab, a monoclonal antibody that selectively targets CD20-positive B-lymphocytes. The subcutaneous route of administration is expected to improve convenience for patients and to reduce healthcare professional resource use compared with conventional intravenous infusion. Various non-clinical and clinical studies were conducted to support the bridge from the approved intravenous formulation to the novel subcutaneous treatment. The underlying hypothesis for these studies was that achieving subcutaneous rituximab serum trough concentrations that are at least as high as those reached with the intravenous formulation would result in at least the same degree of receptor saturation. Preclinical mouse xenograft and cynomolgus monkey B-cell depletion studies were performed at intravenous and subcutaneous doses that were previously found to result in comparable serum concentrations in pharmacokinetic studies in the same species. Results from these non-clinical assessments guided dose selection for the subsequent phase 1b dose finding trials in patients with follicular lymphoma as part of maintenance treatment. A fixed dose of 1 400 mg was found to result in noninferior serum trough concentrations to the intravenous formulation. Clinical trials in the induction setting in patients with follicular lymphoma and chronic lymphocytic leukemia are currently ongoing.
Keywords: clinical trials; dose finding; follicular lymphoma; intravenous; pharmacology; preclinical studies